Assessment of CD8(+) T cell differentiation in Trypanosoma cruzi-infected children - Albareda, María Cecilia (2010)
Fil: Albareda, María Cecilia. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.